Urgensi Digitalisasi Terhadap Stabilitas Sistem Keuangan Di Indonesia - chairul ihsan burhanuddin; Muhammad Nur Abdi; Burhanuddin Burhanuddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
Indonesia's economic progress is in step with the country's financial system's digitalization. The issue with the digitization process is that a financial system model that is compatible with the economy's needs and constraints is required. System tools, literacies, and financial system models, for example. To provide explanations and reinforcement of the material presented, this study employs a qualitative descriptive technique. The viewpoint of banking innovations and the digitalization process in numerous countries is one of them. The study's findings provide an outline of critical issues that must be addressed in order for Indonesia to embrace digitalization in its financial sector. So that the consequences of this digitalization process can guarantee financial stability and the economy's integrity in the future. The correct tools, literacy, and models in the financial system are just a few of the concerns that the government must carefully prepare. Keywords : Digitization, Literacy, Devices, Financial System, Economics.